Representation of the Author’s Inner Conflict in the Novel Ziarah (1969) by Iwan Simatupang: a Psychoanalitycal Study - Elisa Nur Apriliana; Ririn Wahyu Eka Sari; Dwi Susanto (SUAR BETANG, 2023)
The aim of this research is to reveal Iwan Simatupang's inner conflict through his novel entitled Ziarah (1969) using Sigmund Freud's psychoanalytic approach, namely condensation, symbolization, and diversion. The novel tells the story of the inner struggles of a former painter who acts like a madman and a drunkard because his wife died. The method used is descriptive qualitative. The material object in this research is the novel Ziarah (1969) by Iwan Simatupang, while the formal object is the author's inner conflict which is represented through the language contained in the novel. The primary data for this research are words, sentences, language, narrative, and symbols contained in the novel Ziarah (1969) which show the existence of conflict or desire that the author tries to suppress. The secondary data for this research is all information related to the biography and work of Iwan Simatupang to be related to psychology, especially in revealing the inner conflict experienced by Iwan Simatupang. Data collection techniques are carried out by reading and recording various information needed in the research. The data analysis technique uses Sigmund Freud's psychoanalytic theory to uncover the author's inner construction or conflict represented in the text. The results of the research were that Iwan Simatupang was known to be experiencing depression because his wife died. Through condensation, symbolization and diversion, Iwan can be said to be experiencing a serious mental disorder which can affect his emotions, behavior and communication. This mental disorder is called schizophrenia. AbstrakTujuan dari penelitian ini adalah mengungkapkan konflik batin Iwan Simatupang melalui novelnya yang berjudul Ziarah (1969) menggunakan pendekatan psikoanalisis Sigmund Freud, yaitu kondensasi, simbolisasi, dan pengalihan. Novel tersebut bercerita tentang pergulatan batin mantan bekas pelukis yang bertingkah layaknya orang gila dan pemabuk karena istrinya meninggal. Metode yang digunakan adalah deskriptif kualitatif. Objek material dalam penelitian ini adalah novel Ziarah (1969) karya Iwan Simatupang, sedangkan objek formalnya berupa konflik batin pengarang yang direpresentasikan melalui bahasa yang terdapat dalam novel. Data primer penelitian ini berupa kata, kalimat, bahasa, narasi, dan simbol yang terdapat dalam novel Ziarah (1969) yang menunjukkan adanya konflik atau hasrat yang berusaha pengarang pendam. Data sekunder penelitian ini adalah segala informasi yang berhubungan dengan biografi dan karya dari Iwan Simatupang untuk dikaitkan dengan psikologi, khususnya dalam mengungkap konflik batin yang dialami oleh Iwan Simatupang. Teknik pengumpulan data dilakukan dengan cara membaca dan mencatat berbagai informasi yang diperlukan dalam penelitian. Teknik analisis data menggunakan teori psikoanalisis Sigmund Freud untuk membongkar konstruksi atau konflik batin pengarang yang terepresentasi dalam teks. Iwan Simatupang diketahui mengalami depresi karena istrinya meninggal. Melalui kondensasi, simbolisasi, dan pengalihan Iwan dapat dikatakan mengalami gangguan mental berat di mana dapat memengaruhi emosional, tingkah laku, dan komunikasinya. Gangguan mental inilah yang disebut dengan skizofrenia.